Polymer-Functionalized Nanodiamond Platforms as Vehicles for Gene Delivery - Zhang, Xue-Qing; Chen, Mark; Lam, Robert; Xu, Xiaoyang; Osawa, Eiji; Ho, Dean (ACS nano, 2009)
Gene therapy holds great promise for treating diseases ranging from inherited disorders to acquired conditions and cancers. Nonetheless, because a method of gene delivery that is both effective and safe has remained elusive, these successes were limited. Functional nanodiamonds (NDs) are rapidly emerging as promising carriers for next-generation therapeutics with demonstrated potential. Here we introduce NDs as vectors for in vitro gene delivery via surface-immobilization with 800 Da polyethyleneimine (PEI800) and covalent conjugation with amine groups. We designed PEI800-modified NDs exhibiting the high transfection efficiency of high molecular weight PEI (PEI25K), but without the high cytotoxicity inherent to PEI25K. Additionally, we demonstrated that the enhanced delivery properties were exclusively mediated by the hybrid ND−PEI800 material and not exhibited by any of the materials alone. This platform approach represents an efficient avenue toward gene delivery via DNA-functionalized NDs, and serves as a rapid, scalable, and broadly applicable gene therapy strategy.